2008
DOI: 10.4321/s0213-61632008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Neurocognitive correlates of Schizotypy Personality Clusters in healthy individuals

Abstract: -Background and Objectives: Inconsistencies in the relationship between schizotypy dimensions and neurocognitive functions found in correlational studies may be clarified with the use of alternative methodological approaches. The aim of this study was to examine the existence of different profiles of schizotypal traits and their neurocognitIve correlates in non-clinical subjects by means of cluster analysis.Methods: We examined seventy six healthy adults from the general population with a comprehensive neuroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In sum, three studies have observed an inverse relation between productivity in category fluency tasks and, at least, one of the three schizotypy dimensions (Aguilera-Ruíz et al, 2008;Dinzeo et al, 2018;Tan and Rossell, 2017). In contrast, one study has obtained a positive relation between the disorganized dimension and productivity (Minor et al, 2015) and two further studies have failed to show any association between schizotypy and fluency productivity (Hori et al, 2008;Kiang and Kutas, 2006).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In sum, three studies have observed an inverse relation between productivity in category fluency tasks and, at least, one of the three schizotypy dimensions (Aguilera-Ruíz et al, 2008;Dinzeo et al, 2018;Tan and Rossell, 2017). In contrast, one study has obtained a positive relation between the disorganized dimension and productivity (Minor et al, 2015) and two further studies have failed to show any association between schizotypy and fluency productivity (Hori et al, 2008;Kiang and Kutas, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…No effects were observed in the responses to the other three categories (animals, vehicles and articles of clothing) or the mean originality overall. Years later, Aguilera-Ruíz et al (2008) observed an inverse association between positive and negative schizotypy and a composite measure including category fluency and other semantic tasks, whereas Minor and Cohen (2012) reported more original responses for participants with high schizotypy scores. In contrast, Hori et al (2008) observed no association between productivity or originality of the responses to category fluency and schizotypy.…”
Section: Introductionmentioning
confidence: 94%
“…Based on previous research (e.g. Suhr and Spitznagel, 2001 , Aguilera Ruíz et al, 2008 , Barrantes-Vidal et al, 2003 , Goulding, 2005 ) the configuration of the other clusters was predicted to be: predominantly negative schizotypy, and predominantly positive schizotypy. Additionally, this study aimed to determine whether state psychological distress and/or atypical handedness (as a proxy for reduced hemispheric asymmetry) also accounted for the expression of NSS.…”
Section: Introductionmentioning
confidence: 97%
“…Previous schizotypy research has found the number of clusters to vary from three to four-group cluster solutions (e.g. Suhr and Spitznagel, 2001 , Aguilera Ruíz et al, 2008 , Barrantes-Vidal et al, 2003 , Goulding, 2005 ). Most often, clusters were characterized as: high overall schizotypy, positive schizotypy (with unusual perceptual experiences and cognitive disorganization characteristics), negative schizotypy (with introverted and anhedonic characteristics), and low overall schizotypy.…”
Section: Introductionmentioning
confidence: 99%
“…However, from a dimensional perspective (Claridge, 1997), schizotypy is understood as a group of personality traits that are distributed continuously in the general population regardless of their relationship with the development of a pathology. In light of this approach, interest has grown in recent years in the study of the variability of cognitive abilities associated with the greater or lesser presence of schizotypal traits in non-clinical population (Aguilera-Ruíz et al, 2008;Mohr and Claridge, 2015).…”
Section: Introductionmentioning
confidence: 99%